Urban Planning and the Suburbs: Solutions for Sustainability from the Edges - Moos, Markus (2018)
This thematic issue of Urban Planning includes five articles that engage critically with the debates regarding the sustainability of suburbs. Contributions include a long-term perspective of the persistence of automobile-based planning and culture in Canada; an assessment of transportation modes among high-rise condominium apartment residents in Toronto’s outer suburbs; an evaluation of policy prescribed social-mix in France’s banlieues; a study of hyper-diversity in Peel Region in the Greater Toronto Area, which positions suburbs as centers of diversity; and an analysis of how the implementation and governance of new urbanist designs in three US communities has generally failed to achieve social objectives. The articles put into question the common approach of implementing suburban sustainability policy via urbanization and social mix. Together, the contributions point to the need for more stringent restrictions on automobile use, enhanced transit service in the suburbs, emphasis on bottom-up, community-driven policy-making, recognition of multiple dimensions of diversity, and strong political leadership to drive sustainability policy forward.